GRADUATE COURSES IN ACCOUNTING. - Newlove, G. H. (The Accounting Review, 1927)
Abstract The purpose of the present paper is to ascertain just what graduate courses in accounting are offered by the universities listed by the collegiate department of the United States Bureau of Education as giving graduate work in applied economics. In order to simplify the figures, no distinction is made between a term course and a semester course. Likewise, no distinction is made between courses given only to graduates and those given to both graduate and undergraduates; strictly undergraduate courses are ignored. Data presented in the article shows that the graduate courses in accounting are largely concentrated in the basic subjects. While twenty-one different accounting studies are given, 71.7 per cent of the courses are given in the subjects that a student already familiar with the elementary principles of accounting must pursue. In order to become a professional accountant; and although prospective Certified Public Accountants (C.P.A.) candidates form only a small portion of the total number of accounting students, it still is advisable to offer adequate preparation for the C.P.A. examinations. The relatively weak showing of the subjects not absolutely needed in the professional accounting curriculum is due to the fact that accounting must be studied in logical sequence.